African swine fever in the Primorsky Krai: disease situation and molecular and biological properties of the isolate recovered from a wild boar long bone - А. R. Shotin; A. S. Igolkin; Ali Mazloum; I. V. Shevchenko; N. S. Bardina; E. O. Morozova; А. А. Shevtsov (Ветеринария сегодня, 2022)
It is necessary to continue the analysis of the situation and molecular and biological properties of the current African swine fever virus isolates, recovered in the Russian border territories to cover the following tasks: eradication of African swine fever; development of effective disease surveillance and control programs; search for promising genome markers for the vaccine development; implementation of the differentiation strategy between vaccinated and non-vaccinated animals; and clustering of the isolates. The post-hoc analysis of some ASF epidemiological data and comparative genetic analysis of isolates circulating in the Far East Federal District suggested the agent introduction and spread routes, as well as the seasonality of the infection occurrence in the Primorsky Krai. It was established, that two ASFV subgenotypes (IGR-I и IGR-II), differentiated by intergenic region I73R/I329L, circulated in the region under study during the first months post infection. Analysis of biological properties of ASFV/Primorsky 19/WB-6723 isolate recovered from the long bone of a dead wild boar in the Primorsky Krai suggested that the isolate is highly virulent, able to cause peracute to subacute disease and up to 100% mortality among infected animals. The incubation period and duration of the disease course in experimentally infected pigs were 4–6 and 3–5 days post infection, respectively. The ASFV genome was detected in blood samples collected from infected pigs on 5–8 days post infection by real-time polymerase chain reaction. Specific antibodies in blood samples were not detected. The need in further research of molecular and biological properties of current ASFV isolates was reaffirmed. To prevent the continuation of the epizooty and deterioration of the current situation the approaches to the disease surveillance and control need to be modified.